High-strength connecting piece bolt and machining process

Through the composition and processing process of specific materials, the problem of susceptibility to fatigue under harsh conditions is solved, and high -intensity and abrasion resistance bolts are achieved, extending the service life and improving safety.

CN119351898AInactive Publication Date: 2025-01-24JIAXING SHENGLONG HARDWARE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478398.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing bolts are prone to metal fatigue under harsh working conditions, have short service life and pose safety hazards.

Method used

Using materials and processing techniques of specific composition, including a combination of carbon, vanadium, silicon, manganese, aluminum, zirconium and other elements, the strength and wear resistance of the bolts are improved through hot forging, heat treatment and coating with wear-resistant and anti-rust paint. sex.

Benefits of technology

The production of high-strength bolts has been achieved, with a strength of 15.1 and good hardness, plasticity and toughness. It can last for 24 hours in a corrosion test, extending its service life and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351898A_ABST
    Figure CN119351898A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of bolts, and discloses a high-strength connecting piece bolt and a processing technology, and the bolt is prepared from the following components in parts by weight: 1-3% of carbon, 1-4% of vanadium, 1-3% of silicon, 3-7% of manganese, 2-9% of aluminum, 2-6% of zirconium, 8-20% of chromium, 1-6% of cobalt, 1-4% of tungsten, 2-6% of copper, 4-10% of boron, 4-8% of titanium, 2-4% of molybdenum, 1-5% of quartz sand and 2-6% of zinc. According to the technical scheme, the high-strength nut is prepared from the following raw materials in percentage by weight: 2-5% of phosphorus, 2-6% of rare earth elements, 1-2% of niobium, 0.5-1.5% of silicon, 0.1-2.5% of nickel, 0.2-0.35% of nitrogen and the balance of iron and unremovable impurities, the high-strength nut is prepared from simple raw materials, the process is simple, the production difficulty is reduced, production and processing are facilitated, the production efficiency is improved, and by coating the wear-resistant and rust-proof coating, the wear-resistant and rust-proof performance of the high-strength nut is improved. The bolt can be effectively prevented from being abraded and rusted, the service life of the bolt is prolonged, and the bolt is convenient to disassemble.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bolts, and in particular relates to a high-strength connecting bolt and a processing technology. Background Art

[0002] Fasteners play the role of connection, positioning and sealing in mechanical components, among which bolts are the most used. With the continuous enlargement of various types of machinery, equipment, and construction projects, as well as the continuous increase in power and speed, the working conditions of bolt parts have become more severe, and the working stress has increased significantly. Therefore, bolt steel is required to have higher strength. Existing bolts are prone to metal fatigue, have a short service life, and are prone to safety hazards. For this reason, we propose a high-strength connector bolt and processing technology. Summary of the invention

[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high-strength connecting bolt and a processing technology, which effectively solves the above problems.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a high-strength connecting bolt, wherein the material for making the bolt includes the following components in weight proportions: 1-3% carbon, 1-4% vanadium, 1-3% silicon, 3-7% manganese, 2-9% aluminum, 2-6% zirconium, 8-20% chromium, 1-6% cobalt, 1-4% tungsten, 2-6% copper, 4-10% boron, 4-8% titanium, 2-4% molybdenum, 1-5% quartz sand, 2-6% zinc, 2-5% phosphorus, 2-6% rare earth elements, 1-2% niobium, 0.5-1.5% silicon, 0.1-2.5% nickel content, 0.2-0.35% nitrogen content, and the rest is iron and impurities that cannot be removed.

[0005] Preferably, the mixed rare earth RE is a mixture of Nd, Pm, Sm, Yb and Y in a mass ratio of 2-4:1.5-2.5:1:0.8-1.2:0.1-0.5.

[0006] Preferably, an anti-rust layer is provided on the outer side of the bolt, and the thickness of the anti-rust layer is 0.8-1.0 μm.

[0007] A processing technology for high-strength connecting bolts:

[0008] The processing technology specifically includes the following steps:

[0009] S1: Raw material preparation: Produce each raw material into steel wire,

[0010] The wire is soaked in a pickling tank to remove oil and rust stains, and the wire is straightened by a straightening machine, and then cut into steel bars of required length;

[0011] S2: hot upsetting, the steel bar obtained in S1 is heated at high temperature, taken out from the high temperature furnace after heating and rotated to the forging press, and then the punch is started to perform the preliminary forming process of the bolt head, and the punch is started again after completion, so as to finally complete the processing of the bolt head into a row and obtain the bolt blank;

[0012] S3: Auxiliary treatment, using a hydraulic press combined with a trimming die to trim the flash of the bolt head of the bolt blank;

[0013] S4: Semi-finished product cleaning, the oxides and deposits of the semi-finished bolts are removed by machine, and the surface of the semi-finished bolts is cleaned;

[0014] S5: thread processing, applying lubricant to the surface of the semi-finished bolt blank obtained in S4 to reduce friction and other resistance, and then in a thread rolling machine, the thread rolling cylinder of the thread rolling machine rotates to roll threads on the surface of the bolt blank to obtain a finished bolt;

[0015] S6: Heat treatment, the finished bolts are heated by a heating machine, and then a layer of antioxidant is sprayed on them to prevent rust.

[0016] Preferably, chamfering is performed, and the bolt blank obtained in S2 is fed into an extruder, and a chamfer is extruded on the other end of the bolt blank bolt head through the extruder. This chamfer can guide the rotation of the nut and make it easier for the nut to enter the pre-opened screw hole, while also preventing the bolt edge from cutting the fingers of the staff.

[0017] Preferably, the finished bolts of S6 are preheated first, then heated to 1050-1100°C for solution treatment, kept warm for 30-60 minutes, and then water-cooled and quenched to obtain high-strength bolts.

[0018] Preferably, the method for heating the steel bar in S2 is to quench in a quenching furnace with the temperature controlled at 1050-1300°C, the heating time being 10-20min, the holding time being 30-50min, and then high-temperature tempering is performed with the tempering temperature being 750-950°C and the time being 40-70min. Finally, the steel bar is cooled with oil after being taken out of the furnace, and then tempered again to 750-950°C for forging.

[0019] Preferably, the coating is applied thickly on the bolt surface for the first time, and baked while coating. After the first coating, it is evenly baked for 15-25 minutes, and then applied for the second time. The thickness of the second coating is less than the thickness of the first coating. After coating, it is evenly baked again for 10-15 minutes. After the third coating, the thickness of the third coating is less than the thickness of the second coating. After coating, it is evenly baked again for 15-30 minutes until the surface is cured.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The raw materials used in the present invention are simple, and high-strength nuts can be obtained. The process is simple, the production difficulty is reduced, the production and processing are convenient, and the production efficiency is improved. By coating the wear-resistant and rust-proof coating, the wear and rust of the bolts can be effectively prevented, the service life of the bolts can be extended, and the disassembly of the bolts is also convenient;

[0022] 2. The high-strength bolts processed by Example 2 of the present invention have a strength of 15.1, and have good hardness, plasticity and toughness. The bolts treated by the process of the present invention can be tested for up to 24 hours in accordance with the GB / T10125-1997 artificial atmosphere corrosion test-salt spray test, which effectively prolongs the service life of the bolts, makes them more stable during use, reduces the probability of deformation, and improves safety in use;

[0023] 3. The present invention can effectively increase the strength of the threaded portion by quenching at different temperatures, and can increase the strength and wear resistance of the bolt by coating a high-strength coating, thereby improving the strength of the bolt. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0025] In the attached picture:

[0026] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] A high-strength connecting bolt, the material for making the bolt includes the following components in weight proportion: 2% carbon, 3% vanadium, 1.2% silicon, 4% manganese, 6% aluminum, 4% zirconium, 12% chromium, 4% cobalt, 2% tungsten, 3% copper, 5% boron, 3% titanium, 3% molybdenum, 4% quartz sand, 2% zinc, 3% phosphorus, 2% rare earth elements, 1-2% niobium, 0.5% silicon, 0.1% nickel, 0.22% nitrogen, and the rest is iron and impurities that cannot be removed.

[0030] The mixed rare earth is a mixture of Nd, Pm, Sm, Yb and Y in a mass ratio of 3:2:1:1:0.3.

[0031] The outer side of the bolt is provided with an anti-rust layer, and the thickness of the anti-rust layer is 1.0 μm.

[0032] See also Figure 1 , a processing technology for high-strength connecting bolts, comprising the following steps:

[0033] S1: Raw material preparation: various raw materials are produced into steel wires, the steel wires are soaked in a pickling tank to remove oil and rust stains, the steel wires are straightened by a straightening machine, and then cut into steel bars of required length;

[0034] S2: hot upsetting forming, the steel bar obtained in S1 is heated at high temperature. The method for heating the steel bar is to quench it in a quenching furnace, and the temperature is controlled at 1050℃, the heating time is 15min, the holding time is 30-50min, and then high-temperature tempering is performed. The tempering temperature is 750℃ and the time is 50min. Finally, it is cooled with oil after being taken out of the furnace, and then tempered to 850℃ for forging. After the steel bar is heated, it is taken out of the high-temperature furnace and rotated to the forging press, and then the punch is started to perform the preliminary forming processing of the bolt head. After completion, the punch is started again, so as to finally complete the processing of the bolt head into a row, and the obtained bolt blank is sent to the extruder. The other end of the bolt head of the bolt blank is extruded by the extruder to form a chamfer. This chamfer can guide the rotation of the nut so that the nut can be easily entered into the pre-opened screw hole, and it can also prevent the bolt edge from cutting the fingers of the staff, so as to obtain the bolt blank;

[0035] S3: Auxiliary treatment, using a hydraulic press combined with a trimming die to trim the flash of the bolt head of the bolt blank;

[0036] S4: Semi-finished product cleaning, the oxides and deposits of the semi-finished bolts are removed by machine, and the surface of the semi-finished bolts is cleaned;

[0037] S5: thread processing, applying lubricant to the surface of the semi-finished bolt blank obtained in S4 to reduce friction and other resistance, and then in a thread rolling machine, the thread rolling cylinder of the thread rolling machine rotates to roll threads on the surface of the bolt blank to obtain a finished bolt;

[0038] S6: Heat treatment, heating the finished bolts by a heating machine, preheating first, and then heating to 1050℃ for solution treatment, keeping warm for 30 minutes, and then using water cooling quenching treatment to obtain high-strength bolts, and then spraying a layer of antioxidant to prevent rust. The ingredients of the antioxidant are: 32% hexaphosphate, 26% acrylamide, 14% glutamic acid, 10% nano-silicon dioxide, and 7% film-forming aid. Apply the coating thickly on the surface of the bolt for the first time, and bake while applying. After one coating, bake evenly for 15 minutes, apply a second coating, the thickness of the second coating is less than the thickness of the first coating, and after coating, bake evenly again for 10-15 minutes, apply a third coating, the thickness of the third coating is less than the thickness of the second coating, and after coating, bake evenly again for 15-30 minutes until the surface is solidified.

[0039] Embodiment 2:

[0040] A high-strength connecting bolt, the material for making the bolt includes the following components in weight proportions: 2% carbon, 2% vanadium, 2% silicon, 3% manganese, 2% aluminum, 6% zirconium, 13% chromium, 3% cobalt, 2% tungsten, 2% copper, 4% boron, 4% titanium, 2% molybdenum, 1% quartz sand, 2% zinc, 5% phosphorus, 6% rare earth elements, 1% niobium, 0.5% silicon, 0.1% nickel content, 0.3% nitrogen content, and the rest is iron and impurities that cannot be removed.

[0041] The mixed rare earth RE is a mixture of Nd, Pm, Sm, Yb and Y in a mass ratio of 4:1.5:1:0.5.

[0042] The outer side of the bolt is provided with an anti-rust layer, and the thickness of the anti-rust layer is 0.9 μm.

[0043] See also Figure 1 , a processing technology for high-strength connecting bolts, comprising the following steps:

[0044] S1: Raw material preparation: various raw materials are produced into steel wires, the steel wires are soaked in a pickling tank to remove oil and rust stains, the steel wires are straightened by a straightening machine, and then cut into steel bars of required length;

[0045] S2: hot upsetting forming, the steel bar obtained in S1 is heated at high temperature. The steel bar heating method is to quench in a quenching furnace, the temperature of which is controlled at 1100°C, the heating time is 10 minutes, the holding time is 40 minutes, and then high-temperature tempering is performed, the tempering temperature is 850°C, the time is 50 minutes, and finally the steel bar is cooled with oil after being taken out of the furnace, and then tempered to 850°C for forging. After the steel bar is heated, it is taken out of the high-temperature furnace and rotated to the forging press, and then the punch is started to perform the preliminary forming processing of the bolt head. After completion, the punch is started again, so as to finally complete the processing of the bolt head into a row, and the obtained bolt blank is sent to the extruder, and a chamfer is extruded on the other end of the bolt head of the bolt blank through the extruder. This chamfer can guide the rotation of the nut so that the nut can be easily entered into the pre-opened screw hole, and it can also prevent the bolt edge from cutting the fingers of the staff, so as to obtain the bolt blank;

[0046] S3: Auxiliary treatment, using a hydraulic press combined with a trimming die to trim the flash of the bolt head of the bolt blank;

[0047] S4: Semi-finished product cleaning, the oxides and deposits of the semi-finished bolts are removed by machine, and the surface of the semi-finished bolts is cleaned;

[0048] S5: thread processing, applying lubricant to the surface of the semi-finished bolt blank obtained in S4 to reduce friction and other resistance, and then in a thread rolling machine, the thread rolling cylinder of the thread rolling machine rotates to roll threads on the surface of the bolt blank to obtain a finished bolt;

[0049] S6: Heat treatment, heating the finished bolts by a heating machine, preheating first, and then heating to 1100°C for solution treatment, keeping warm for 50 minutes, and then using water cooling quenching treatment to obtain high-strength bolts, and then spraying a layer of antioxidant to prevent rust. The ingredients of the antioxidant are: 30% hexaphosphate, 30% acrylamide, 18% glutamic acid, 12% nano-silicon dioxide, and 10% film-forming aid. Apply the coating thickly on the surface of the bolt for the first time, and bake while applying. After one coating, bake evenly for 25 minutes, apply a second coating, the thickness of the second coating is less than the thickness of the first coating, and after coating, bake evenly for 15 minutes again, apply a third coating, the thickness of the third coating is less than the thickness of the second coating, and after coating, bake evenly for 30 minutes again until the surface is solidified.

[0050] Embodiment 3:

[0051] A high-strength connecting bolt, the material for making the bolt includes the following components in parts by weight: 1.5% carbon, 1.5% vanadium, 2.5% silicon, 3.5% manganese, 2.5% aluminum, 5% zirconium, 13% chromium, 4.5% cobalt, 3% tungsten, 4% copper, 5% boron, 5% titanium, 5% molybdenum, 3% quartz sand, 3% zinc, 3% phosphorus, 3% rare earth elements, 1% niobium, 1% silicon, 2% nickel, 0.25% nitrogen, and the rest is iron and impurities that cannot be removed.

[0052] The mixed rare earth RE is a mixture of Nd, Pm, Sm, Yb and Y in a mass ratio of 3:1.5:1:1.2:0.3.

[0053] The outer side of the bolt is provided with an anti-rust layer, and the thickness of the anti-rust layer is 0.9 μm.

[0054] See also Figure 1 , a processing technology for high-strength connecting bolts, comprising the following steps:

[0055] S1: Raw material preparation: various raw materials are produced into steel wires, the steel wires are soaked in a pickling tank to remove oil and rust stains, the steel wires are straightened by a straightening machine, and then cut into steel bars of required length;

[0056] S2: hot upsetting forming, the steel bar obtained in S1 is heated at high temperature. The method for heating the steel bar is to quench it in a quenching furnace, and the temperature is controlled at 1200℃, the heating time is 15min, the holding time is 45min, and then high-temperature tempering is performed, the tempering temperature is 800℃, the time is 55min, and finally it is cooled with oil after being taken out of the furnace, and then tempered to 850℃ for forging. After the steel bar is heated, it is taken out of the high-temperature furnace and rotated to the forging press, and then the punch is started to perform the preliminary forming processing of the bolt head. After completion, the punch is started again, so as to finally complete the processing of the bolt head into a row, and the obtained bolt blank is sent to the extruder, and a chamfer is extruded on the other end of the bolt head of the bolt blank through the extruder. This chamfer can guide the rotation of the nut so that the nut can be easily entered into the pre-opened screw hole, and it can also prevent the bolt edge from cutting the fingers of the staff, so as to obtain the bolt blank;

[0057] S3: Auxiliary treatment, using a hydraulic press combined with a trimming die to trim the flash of the bolt head of the bolt blank;

[0058] S4: Semi-finished product cleaning, the oxides and deposits of the semi-finished bolts are removed by machine, and the surface of the semi-finished bolts is cleaned;

[0059] S5: thread processing, applying lubricant to the surface of the semi-finished bolt blank obtained in S4 to reduce friction and other resistance, and then in a thread rolling machine, the thread rolling cylinder of the thread rolling machine rotates to roll threads on the surface of the bolt blank to obtain a finished bolt;

[0060] S6: Heat treatment, heating the finished bolts by a heating machine, preheating first, and then heating to 1050℃ for solution treatment, keeping warm for 50 minutes, and then using water cooling quenching treatment to obtain high-strength bolts, and then spraying a layer of antioxidant to prevent rust. The ingredients of the antioxidant are: 335% hexaphosphate, 27% acrylamide, 17% glutamic acid, 14% nano-silicon dioxide, and 9% film-forming aid. Apply the coating thickly on the surface of the bolt for the first time, and bake while applying. After one coating, bake evenly for 22 minutes, apply a second coating, the thickness of the second coating is less than the thickness of the first coating, and after coating, bake evenly for 103 minutes again, apply a third coating, the thickness of the third coating is less than the thickness of the second coating, and after coating, bake evenly for 27 minutes again until the surface is solidified.

[0061] Embodiment 4:

[0062] A high-strength connecting bolt, the material for making the bolt includes the following components in weight proportions: 2% carbon, 3% vanadium, 5% silicon, 5% manganese, 7% aluminum, 4% zirconium, 14% chromium, 5% cobalt, 3% tungsten, 4% copper, 6% boron, 5% titanium, 3% molybdenum, 4% quartz sand, 4% zinc, 4% phosphorus, 4% rare earth elements, 1% niobium, 1% silicon, 0.7% nickel, 0.3% nitrogen, and the remainder is iron and impurities that cannot be removed.

[0063] The mixed rare earth RE is a mixture of Nd, Pm, Sm, Yb and Y in a mass ratio of 3:2:1:1:0.25.

[0064] The outer side of the bolt is provided with an anti-rust layer, and the thickness of the anti-rust layer is 0.9 μm.

[0065] See also Figure 1 , a processing technology for high-strength connecting bolts, comprising the following steps:

[0066] S1: Raw material preparation: various raw materials are produced into steel wires, the steel wires are soaked in a pickling tank to remove oil and rust stains, the steel wires are straightened by a straightening machine, and then cut into steel bars of required length;

[0067] S2: hot upsetting forming, the steel bar obtained in S1 is heated at high temperature. The method for heating the steel bar is to quench it in a quenching furnace, and the temperature is controlled at 1150℃, the heating time is 15min, the holding time is 40min, and then high-temperature tempering is performed, the tempering temperature is 800℃, the time is 50min, and finally it is cooled with oil after being taken out of the furnace, and then tempered to 850℃ for forging. After the steel bar is heated, it is taken out of the high-temperature furnace and rotated to the forging press, and then the punch is started to perform the preliminary forming processing of the bolt head. After completion, the punch is started again, so as to finally complete the processing of the bolt head into a row, and the obtained bolt blank is sent to the extruder, and the other end of the bolt head of the bolt blank is extruded by the extruder to form a chamfer. This chamfer can guide the rotation of the nut so that the nut can be easily entered into the pre-opened screw hole, and it can also prevent the bolt edge from cutting the fingers of the staff, so as to obtain the bolt blank;

[0068] S3: Auxiliary treatment, using a hydraulic press combined with a trimming die to trim the flash of the bolt head of the bolt blank;

[0069] S4: Semi-finished product cleaning, the oxides and deposits of the semi-finished bolts are removed by machine, and the surface of the semi-finished bolts is cleaned;

[0070] S5: thread processing, applying lubricant to the surface of the semi-finished bolt blank obtained in S4 to reduce friction and other resistance, and then in a thread rolling machine, the thread rolling cylinder of the thread rolling machine rotates to roll threads on the surface of the bolt blank to obtain a finished bolt;

[0071] S6: Heat treatment, heating the finished bolts by a heating machine, preheating first, and then heating to 1100℃ for solution treatment, keeping warm for 50 minutes, and then using water cooling quenching treatment to obtain high-strength bolts, and then spraying a layer of antioxidant to prevent rust. The ingredients of the antioxidant are: 29% hexaphosphate, 29% acrylamide, 18% glutamic acid, 14% nano-silicon dioxide, and 10% film-forming aid. Apply the coating thickly on the surface of the bolt for the first time, and bake while applying. After one coating, bake evenly for 20 minutes, apply a second coating, the thickness of the second coating is less than the thickness of the first coating, and after coating, bake evenly for 13 minutes again, apply a third coating, the thickness of the third coating is less than the thickness of the second coating, and after coating, bake evenly for 21 minutes again until the surface is solidified.

[0072] The raw materials used in the present invention are simple, and high-strength nuts can be obtained. The process is simple, the production difficulty is reduced, production and processing are convenient, and production efficiency is improved. By coating a wear-resistant and rust-proof coating, the bolts can be effectively prevented from wearing and rusting, the service life of the bolts is extended, and the disassembly of the bolts is also convenient.

[0073] The high-strength bolts processed by Example 2 of the present invention have a strength of 15.1, and have good hardness, plasticity and toughness. The bolts treated by the process of the present invention can be tested for up to 24 hours in accordance with the artificial atmosphere corrosion test-salt spray test of GB / T10125-1997, which effectively extends the service life of the bolts, makes them more stable during use, reduces the probability of deformation, and improves safety in use.

[0074] The present invention can effectively increase the strength of the threaded part by quenching at different temperatures, and can increase the strength and wear resistance of the bolt by coating a high-strength coating, thereby improving the strength of the bolt.

Claims

1. A high-strength connecting bolt, characterized in that: The materials for making the bolts include the following components in weight proportions: 1-3% carbon, 1-4% vanadium, 1-3% silicon, 3-7% manganese, 2-9% aluminum, 2-6% zirconium, 8-20% chromium, 1-6% cobalt, 1-4% tungsten, 2-6% copper, 4-10% boron, 4-8% titanium, 2-4% molybdenum, 1-5% quartz sand, 2-6% zinc, 2-5% phosphorus, 2-6% rare earth elements, 1-2% niobium, 0.5-1.5% silicon, 0.1-2.5% nickel, 0.2-0.35% nitrogen, and the rest is iron and impurities that cannot be removed.

2. A high-strength connecting bolt according to claim 1, characterized in that: The mixed rare earth RE is a mixture of Nd, Pm, Sm, Yb and Y in a mass ratio of 2-4:1.5-2.5:1:0.8-1.2:0.1-0.

5.

3. The high-strength connecting bolt according to claim 1, characterized in that: The outer side of the bolt is provided with an anti-rust layer, and the thickness of the anti-rust layer is 0.8-1.0 μm.

4. The processing technology of a high-strength connecting bolt according to claim 1, characterized in that: The processing technology specifically includes the following steps: S1: Raw material preparation: various raw materials are produced into steel wires, the steel wires are soaked in a pickling tank to remove oil and rust stains, the steel wires are straightened by a straightening machine, and then cut into steel bars of required length; S2: hot upsetting, the steel bar obtained in S1 is heated at high temperature, taken out from the high temperature furnace after heating and rotated to the forging press, and then the punch is started to perform the preliminary forming process of the bolt head, and the punch is started again after completion, so as to finally complete the processing of the bolt head into a row and obtain the bolt blank; S3: Auxiliary treatment, using a hydraulic press combined with a trimming die to trim the flash of the bolt head of the bolt blank; S4: Semi-finished product cleaning, the oxides and deposits of the semi-finished bolts are removed by machine, and the surface of the semi-finished bolts is cleaned; S5: thread processing, applying lubricant to the surface of the semi-finished bolt blank obtained in S4 to reduce friction and other resistance, and then in a thread rolling machine, the thread rolling cylinder of the thread rolling machine rotates to roll threads on the surface of the bolt blank to obtain a finished bolt; S6: Heat treatment, the finished bolts are heated by a heating machine, and then a layer of antioxidant is sprayed on them to prevent rust.

5. A processing technology for high-strength connecting bolts according to claim 4, characterized in that: Chamfering: The bolt blank obtained by S2 is sent to an extruder, and a chamfer is extruded on the other end of the bolt head of the bolt blank through the extruder. This chamfer can guide the rotation of the nut and make it easier for the nut to enter the pre-opened screw hole. At the same time, it can also prevent the bolt edge from cutting the fingers of the staff.

6. A processing technology for high-strength connecting bolts according to claim 4, characterized in that: The finished S6 bolts are preheated, then heated to 1050-1100°C for solution treatment, kept warm for 30-60 minutes, and then water-cooled quenched to obtain high-strength bolts.

7. A processing technology for high-strength connecting bolts according to any one of claim 4, characterized in that: The antioxidant comprises: 30-35% hexaphosphate, 25-30% acrylamide, 14-18% glutamic acid, 10-14% nano silicon dioxide and 7-10% film-forming aid.

8. A processing technology for high-strength connecting bolts according to any one of claim 4, characterized in that: The method for heating the steel bars in S2 is to quench them in a quenching furnace with a temperature controlled at 1050-1300°C, a heating time of 10-20min, a holding time of 30-50min, and then high-temperature tempering at 750-950°C for 40-70min. Finally, they are cooled with oil after being taken out of the furnace, and then tempered again to 750-950°C for forging.

9. A processing technology for high-strength connecting bolts according to any one of claim 4, characterized in that: Apply the paint thickly on the bolt surface for the first time, and bake it while applying. After the first application, bake it evenly for 15-25 minutes, apply it for the second time, and the thickness of the second application is less than the thickness of the first application. After application, bake it evenly for 10-15 minutes again, apply it for the third time, and the thickness of the third application is less than the thickness of the second application. After application, bake it evenly for 15-30 minutes again until the surface is cured.